Nutrient supply controls the linkage between species abundance and ecological interactions in marine bacterial communities - Dai, Tianjiao; Wen, Donghui; Bates, Colin T.; Wu, Linwei; Guo, Xue; Liu, Suo; Su, Yifan; Lei, Jiesi; Zhou, Jizhong; Yang, Yunfeng (Nature communications, 2022)
Nutrient scarcity is pervasive for natural microbial communities, affecting species reproduction and co-existence. However, it remains unclear whether there are general rules of how microbial species abundances are shaped by biotic and abiotic factors. Here we show that the ribosomal RNA gene operon ( rrn ) copy number, a genomic trait related to bacterial growth rate and nutrient demand, decreases from the abundant to the rare biosphere in the nutrient-rich coastal sediment but exhibits the opposite pattern in the nutrient-scarce pelagic zone of the global ocean. Both patterns are underlain by positive correlations between community-level rrn copy number and nutrients. Furthermore, inter-species co-exclusion inferred by negative network associations is observed more in coastal sediment than in ocean water samples. Nutrient manipulation experiments yield effects of nutrient availability on rrn copy numbers and network associations that are consistent with our field observations. Based on these results, we propose a “hunger games” hypothesis to define microbial species abundance rules using the rrn copy number, ecological interaction, and nutrient availability. Environmental and biotic factors control ecological communities. Here, the authors study community ribosomal rRNA gene copy number in coastal sediment and ocean bacterial communities, and in microcosm nutrient addition experiments, to propose a conceptual framework of how nutrient supply and ecological interactions shape the community.